2022
DOI: 10.3389/fmicb.2022.945972
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer via OMVs co-carrying virulence and antimicrobial-resistant genes is a novel way for the dissemination of carbapenem-resistant hypervirulent Klebsiella pneumoniae

Abstract: IntroductionThe rapidly increased isolation rate of CR-HvKP worldwide has brought great difficulties in controlling clinical infection. Moreover, it has been demonstrated that the transmission of drug-resistant genes among bacteria can be mediated by outer membrane vesicles (OMVs), which is a new way of horizontal gene transfer (HGT). The transmission of virulence genes among bacteria has also been well studied; however, it remains unclear whether virulence and drug-resistant genes can be co-transmitted simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Today, three canonical mechanisms of HGT are recognized, including transformation, transduction, and conjugation ( Dubnau and Blokesch, 2019 ). Also, there are other non-canonical mechanisms including vesiduction, which involves secretion and uptake of EV ( Li P. et al., 2022 ; Marinacci et al., 2023 ). In stressing habitats such as the nosocomial habitat, genome evolution is driven by antibiotic selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, three canonical mechanisms of HGT are recognized, including transformation, transduction, and conjugation ( Dubnau and Blokesch, 2019 ). Also, there are other non-canonical mechanisms including vesiduction, which involves secretion and uptake of EV ( Li P. et al., 2022 ; Marinacci et al., 2023 ). In stressing habitats such as the nosocomial habitat, genome evolution is driven by antibiotic selection.…”
Section: Discussionmentioning
confidence: 99%
“…Of the DNA that is transferred, there are genes associated with AMR, which has huge clinical implications since the potential of propagation of a gene depends to a great extent on the competence to transmit ( Chatterjee et al., 2017 ; Wagner et al., 2018 ). Earlier studies have reported the transfer by EV of a penicillin resistance gene in Neisseria gonorrhoeae ( Dorward et al., 1989 ); the bla OXA-24 ( Rumbo et al., 2011 ) and the bla NDM-1 carbapenemase genes in Acinetobacter baumannii ( Chatterjee et al., 2017 ); the bla CTX-M-15 and bla TEM-1 genes in E. coli O104:H4 ( Bielaszewska et al., 2020 ); and finally, the bla NDM , bla KPC , bla SHV , bla CTX-M-9 , and aac(6′)-Ib genes in K. pneumoniae strains ( Li P. et al., 2022 ). In the present study, we wonder about the ability of the E. coli M19736 clinical strain belonging to the sporadic clone ST615, which was one of the first isolates harboring the mcr-1 gene in Latin America ( Tijet et al., 2017 ), to adapt to the XDR phenotype ( Magiorakos et al., 2012 ) by conjugation and/or transformation assays.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of K. pneumoniae genetic lineages exhibiting both high virulence and carbapenem resistance can occur by several pathways associated with horizontal gene transfer [ 43 , 48 ], and the conjugation was considered its most significant mechanism [ 49 ]. Hypervirulent isolates can acquire MDR plasmids, and MDR isolates can also acquire plasmids carrying virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…The CR-hvKP NUHL 30457, KP4089, the transformant, and EC600 were transferred to the Bioscreen C-Pro fully automated growth curve analyzer for continuous measurement of strain OD, as previously described ( 13 ).…”
Section: Methodsmentioning
confidence: 99%